Peran Digitalisasi Akuntansi dan Pemanfaatan E-Commerce dalam Menciptakan Keunggulan Bersaing UMKM Kuliner yang Dikelola Generasi Z di Kota Malang - Safira, Faiza Meila; Amin, Moh.; Junaidi, Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2026)
The purpose of this study is to investigate and evaluate how the competitive advantage of culinary Micro, Small, and Medium Enterprises (MSMEs) run by Generation Z in Malang City is affected by accounting digitization and e-commerce. This study employs a survey method in conjunction with a quantitative approach. 120 Generation Z culinary MSME owners were given questionnaires to complete in order to gather primary data. The findings demonstrate that e-commerce and accounting digitalization significantly and favorably impact competitive advantage. According to this study, improving the competitiveness of culinary MSMEs requires the use of digital technologies in online marketing and financial administration.Keywords: Accounting digitalization, e-commerce, competitive advantage, culinary msmes, generation z.Top of FormBottom of Form